A new method of placing nasogastric tubes in patients at high risk of epistaxis - Ilse M Novis; Edward Le; Hailey S Novis; Karim Sorour; Khaled A Sorour (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2022)
Nasogastric tubes are used for a multitude of purposes, however, due to their firm composition, they often injure the nasal passages when being placed. While a small amount of bleeding from the nasal mucosa is traditionally acceptable, that small amount of bleeding from the nose can potentially form thrombi that could compromise the airway in patients with impaired sensorium and swallowing.